BNT162b2 COVID-19 vaccination elicited protective robust immune responses in pediatric patients with inborn errors of metabolism - Zubarioglu, Tanyel; Dinc, Harika Oyku; Hopurcuoglu, Duhan; Gulmez, Ruveyda; Uygur, Esma; Yilmaz, Gizem; Ahmadzada, Saffa; Uzunyayla-Inci, Gozde; Oge-Enver, Ece; Kiykim, Ertugrul; Kocazeybek, Bekir; Aktuglu-Zeybek, Cigdem (Frontiers in Immunology, 2023)
Introduction SARS-CoV-2 infection can lead to a life-threatening acute metabolic decompensation in children with inborn errors of metabolism (IEM), so vaccination is mandatory. However, IEMs can also impair innate or adaptive immunity, and the impact of these immune system alterations on immunogenicity and vaccine efficacy is still unknown. Here, we investigated humoral immune responses to the BNT162b2 mRNA COVID-19 vaccine and clinical outcomes in pediatric IEM patients. Methods Fifteen patients between 12-18 years of age with a confirmed diagnosis of IEM, and received BNT162b2 were enrolled to the study. Patients with an anti-SARS-CoV-2 IgG concentration >50 AU/mL before vaccination were defined as “COVID-19 recovered” whereas patients with undetectable anti-SARS-CoV-2 IgG concentration were defined as “COVID-19 naïve”. Anti-SARS-CoV-2 Immunoglobulin G (IgG) and SARS-CoV-2 neutralizing antibody (nAb) titers were measured to assess humoral immune response. Results Anti-SARS-CoV-2 IgG titers and nAb IH% increased significantly after the first dose. The increase in antibody titers after first and second vaccination remained significant in COVID-19 naïve patients. Complete anti-SARS-CoV-2 IgG seropositivity and nAb IH% positivity was observed in all patients after the second dose. Vaccination appears to be clinically effective in IEM patients, as none of the patients had COVID-19 infection within six months of the last vaccination. Discussion Humoral immune response after two doses of BNT162b2 in pediatric IEM patients was adequate and the immune response was not different from that of healthy individuals.